Optical solitons in multiple-core couplers with the nearest neighbors linear coupling - Al Qurashi, Maysaa Mohamed; Ates, Esma; İnç, Mustafa (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
This paper addresses a type of nonlinear directional optical couplers with four different forms, namely the Kerr law, power law, parabolic law and dual similar to power law. The multiple-core couplers with the nearest neighbors linear coupling is studied with four forms of nonlinearity. Bright and dark optical solitons are obtained as well as Jacobi elliptic function solutions. The constraint conditions are acquired for the existence of solitons. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Optical solitons; Optical couplers; Jacobi elliptic functions